2016
DOI: 10.1039/c6cs00361c
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent iodine(iii) fluorinations of alkenes and diazo compounds: new opportunities in fluorination chemistry

Abstract: The fluorination of organic molecules is a rapidly evolving and exciting field in synthesis, which still poses huge challenges despite the advances made in the past decades. Hypervalent iodine(iii) reagents, which have already proven their versatility as synthetic tools in organic chemistry, are currently on the rise in fluorination chemistry. With their ability to break new mechanistic grounds, they grant access to completely new reactivities and thus also to novel fluorinated structural scaffolds. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(95 citation statements)
references
References 161 publications
1
83
0
1
Order By: Relevance
“…2). A single-crystal X-ray study of 9 revealed that this compound also has T-shaped geometry with the Cl1-I1-Cl2 angle of 170.12 (5) o . Compound 9 has a pseudocyclic structure with an intramolecular interaction of 3.084(8) Å between the iodine center and the alkoxy group oxygen atom (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). A single-crystal X-ray study of 9 revealed that this compound also has T-shaped geometry with the Cl1-I1-Cl2 angle of 170.12 (5) o . Compound 9 has a pseudocyclic structure with an intramolecular interaction of 3.084(8) Å between the iodine center and the alkoxy group oxygen atom (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, (dichloroiodo)arenes, ArICl 2 , are commonly applied as efficient oxidants or chlorinating reagents. 8 (Dichloroiodo)benzene 1 is one of the most common reagents that can be conveniently prepared by direct chlorination of iodobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…However, in both cases the product selectivity is poor and the alkene-types amenable to the reaction are limited, with success demonstrated on only very simple substrates. Yoneda employed p-tolyl difluoro l 3iodane (1 a) as the oxidant, [13,14] which improved product selectivity, however 1 a is light-and temperature-sensitive, highly hygroscopic and expensive. [15] Thus, the in situ formation of 1 a using aryl-iodide, HF-salts and Selectfluor or mCPBA, was the subject of elegant work by both Gilmour [16] and Jacobsen.…”
mentioning
confidence: 99%
“…There is a consensus in the community that given the wideranging applications of fluorine in design of bioactive molecules and molecular imaging through positron emission tomography (PET), there is still a strong demand for further development of new synthetic methodologies to expand the chemist's toolbox for easier access to a broader scope of fluorinated and radiochemical compounds. [9] There have been significant recent developments in the area of nucleophilic fluorination, a more accessible form of fluorination, and their application to radiochemistry with [ 18 F]fluoride, such as synthesis of aryl fluorides directly from the corresponding phenols, [10] hypervalent iodine reagents used as fluorine sources in fluorocyclization reactions, [11,12] radiofluorination of diaryliodonium salts and Cu-catalyzed mesityl-aryl-iodonium precursors, [13] metal-catalyzed aryl fluoride bond formation, [14] and recent reviews on these advances and their limitations. [15] Despite the development of modern fluorination techniques, many challenges still exist in terms of limited substrate scope, lack of functional group tolerance, difficulty in synthesizing the precursors and their stability, and the need for strict control of synthesis conditions.…”
mentioning
confidence: 99%